Seed Regeneration Potential of Canopy Gaps at Early Formation Stage in Temperate Secondary Forests, Northeast China - Yan, Qiao-Ling; Zhu, Jiao-Jun; Yu, Li-Zhong (PLOS ONE, 2012)
Promoting the seed regeneration potential of secondary forests undergoing gap disturbances is an important approach for achieving forest restoration and sustainable management. Seedling recruitment from seed banks strongly determines the seed regeneration potential, but the process is poorly understood in the gaps of secondary forests. The objectives of the present study were to evaluate the effects of gap size, seed availability, and environmental conditions on the seed regeneration potential in temperate secondary forests. It was found that gap formation could favor the invasion of more varieties of species in seed banks, but it also could speed up the turnover rate of seed banks leading to lower seed densities. Seeds of the dominant species, Fraxinus rhynchophylla, were transient in soil and there was a minor and discontinuous contribution of the seed bank to its seedling emergence. For Quercus mongolica, emerging seedling number was positively correlated with seed density in gaps (R = 0.32, P<0.01), especially in medium and small gaps (<500 m2). Furthermore, under canopies, there was a positive correlation between seedling number and seed density of Acer mono (R = 0.43, P<0.01). Gap formation could promote seedling emergence of two gap-dependent species (i.e., Q. mongolica and A. mono), but the contribution of seed banks to seedlings was below 10% after gap creation. Soil moisture and temperature were the restrictive factors controlling the seedling emergence from seeds in gaps and under canopies, respectively. Thus, the regeneration potential from seed banks is limited after gap formation.